Association Between COVID-19 and ABO Blood Groups: An Analysis on Convalescent Plasma Donors in Turkey - Mustafa Yilmaz; Aziz Karaca; Nazli Nadire Sozmen; Mustafa Nuri Guncikan; Gizem Gokce Karadag; Nurettin Hafizoglu; Kerem Kinik; Fatma Meric Yilmaz (Haseki Tıp Bülteni)

(untitled)
Aim:To investigate if there is an association between the blood groups of convalescent plasma (CP) donors and Severe acute respiratory syndrome Coronavirus-2 infection risk.Methods:Blood groups of 30605 CP donors were compared with 1316676 Turkish Red Crescent (TRC) whole blood donors. Software data of TRC for the period between 07 April 2020 and 11 December 2020 was analyzed as a retrospective cohort study.Results:Coronavirus disease-2019 (COVID-19) infection risks were higher in A (46.1% vs. 41.6%, p=0.001), AB (8.3% vs. 7.6%, p=0.001), Rh (+) (89.2% vs. 87.5%, p=0.001), A Rh (+) (41.1% vs. 36.6%, p=0.001) and AB Rh (+) (7.4% vs. 6.6%, p=0.001) groups; they were lower in O (29.8% vs. 34.4%, p=0.001), B (15.9% vs. 16.4%, p=0.008), Rh (-) (10.8% vs. 12.5%, p=0.001), B Rh (-) (1.7% vs. 2.0%, p=0.001), O Rh (+) (26.6% vs. 29.9%, p=0.001) and O Rh (-) (3.2% vs. 4.5%, p=0.001) groups.Conclusions:There might be an increased COVID-19 risk in A, AB, Rh (+) and A Rh (+) and AB Rh (+) groups as well as a decreased risk in O, B, Rh (-) and O Rh (+), O Rh (-) and B Rh (-) groups.